2019
DOI: 10.2903/j.efsa.2019.5844
|View full text |Cite
|
Sign up to set email alerts
|

Statement complementing the EFSA Scientific Opinion on application (EFSA‐GMO‐UK‐2006‐34) for authorisation of food and feed containing, consisting of and produced from genetically modified maize 3272

Abstract: Following a request from the European Commission, the GMO Panel assessed additional information related to the application for authorisation of food and feed containing, consisting of and produced from genetically modified (GM) maize 3272 (EFSA- GMO-UK-2006-34). The applicant conducted new agronomic, phenotypic and compositional analysis studies on maize 3272 and assessed the allergenic potential of AMY797E protein, addressing elements that remained inconclusive from previous EFSA opinion issued in 2013. The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Discovering a potentially allergenic protein presents several risk management and communication options (MHLW, 2020;National Agrifood Health and Quality Service, 2002). The regulatory body can choose to disregard the allergenicity and permit the food to be marketed or to ban it entirely (EFSA GMO Panel, 2019b). In response, manufacturers may contemplate modifying the product, accordingly or gathering more safety evidence (EFSA GMO Panel, 2019b).…”
Section: Why and How To Bother With Allergenicity Assessment?mentioning
confidence: 99%
See 1 more Smart Citation
“…Discovering a potentially allergenic protein presents several risk management and communication options (MHLW, 2020;National Agrifood Health and Quality Service, 2002). The regulatory body can choose to disregard the allergenicity and permit the food to be marketed or to ban it entirely (EFSA GMO Panel, 2019b). In response, manufacturers may contemplate modifying the product, accordingly or gathering more safety evidence (EFSA GMO Panel, 2019b).…”
Section: Why and How To Bother With Allergenicity Assessment?mentioning
confidence: 99%
“…The regulatory body can choose to disregard the allergenicity and permit the food to be marketed or to ban it entirely (EFSA GMO Panel, 2019b). In response, manufacturers may contemplate modifying the product, accordingly or gathering more safety evidence (EFSA GMO Panel, 2019b). The second line of defense involves mandatory labeling of major allergens on product packaging, which enables IDFA to make informed choices (FDA, 2021h).…”
Section: Why and How To Bother With Allergenicity Assessment?mentioning
confidence: 99%
“…Practical motivation embraces the optimization of the trajectories in the field with a consequent reduction in the use of fuel and fertilizer, waste of pesticides, and labour hours [26,30]. In the present case study, located in eastern Lombardy (Italy), maize production is experiencing relevant variability, being caused mainly by the low price on the market and pest control regulations and limits, which results in increased imports from countries outside the EU [31]. It was observed that dairy farmers hardly adhere to the organic recommended fertilizer application rates due to the high availability of manure and slurry [28,[32][33][34][35][36]; however, to ensure high crop yields, topdressing mineral N is used despite the purchase and environmental costs [37].…”
Section: Introductionmentioning
confidence: 99%